Efficacy and safety of viscosupplementation with hyaluronic acid for hip osteoarthritis: results from a cross-sectional study with a minimum follow-up of 4 years - Schiavi, Paolo; Calderazzi, Filippo; Pedrini, Martina Francesca; Tacci, Fabrizio; Vaienti, Enrico; Pogliacomi, Francesco (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Osteoarthritis is the most common cause of disability in elderly. Hip osteoarthritis is the second most frequent form affecting a large joint and the social and economic impact on society of its related disability is expected to increase. The purpose of this study was to verify the efficacy and safety of ultrasound-guided viscosupplementation with high weight hyaluronic acid in hip osteoarthritis.Methods: 183 patients with painful hip OA (Kellgren-Lawrence 1-2-3) were treated from January 2014 to December 2016 with viscosupplementation. Patients were evaluated before injection (T0) and after 1,2,3,4 years through the VAS scale and Harris Hip Score (HHS). Patients who underwent to subsequent injections were followed and assessed. Subjects who underwent prosthesis were analyzed for a minimum of 6 months in order to detect any early postoperative complication.Results: The mean improvement of HHS and VAS between T0 and T1 was statistically significant. Patients who underwent subsequent injections showed a higher improvement even if statistical significance was not observed. Results showed that patients with grade 2 of osteoarthritis had the higher change in the scores. No adverse effects were registered. No early complications were reported in those patients who needed prosthesis.Discussion and Conclusions: Results observed confirm that ultrasound-guided viscosupplementation with high weight hyaluronic acid could be a possibility in the treatment of hip osteoarthritis, especially in patients with Kellgren-Lawrence grade 2 of disease. Subsequent injections are not characterized by similar positive effects. Outcomes of prosthetic surgery are not influenced by viscosupplementation.